Smart distributed embedded systems for healthcare applications - Nagrath, Preeti, (ed.); Alzubi, Jafar,(ed.); Singhla, Bhawna,(ed.); Rodrigues, Joel,(ed.); Verma, A. K.(ed.) (Boca Raton C R C press, 2023)
"The text covers new techniques that will be helpful for patient's early diagnosis of diseases and start treatments with the help of distributed technology. It will serve as an ideal reference text for graduate students and researchers in diverse engineering fields including electrical, electronics and communication, computer, and biomedical"--
Keywords: Medical Informatics Applications; Artificial Intelligence; Electronic Health Records--organization & administration; Computer Communication Networks; Virtual Reality